Electron spectroscopic studies of iron and iridium silicides - Probst, Marc; Denecke, Reinhard; Whelan, Caroline; Kinne, Martin; Borgmann, Dieter; Steinrück, Hans-Peter (Surface and Interface Analysis, 2002)
The formation of iron and iridium silicides was studied by means of highly resolved photoelectron spectroscopy of core and valence levels as well as by means of low-energy electron diffraction (LEED). The experiments were carried out at BESSY II in Berlin using synchrotron radiation for the photoemission studies. After evaporation of seven monolayers of Fe on Si(111) at room temperature and annealing to 410 K for 420 s, an ordering of the surface structure and the formation of an (1 × 1) LEED pattern is observed. Upon further heating to 500 K a strong change in both UPS and XPS spectra occurs. This behaviour is attributed to the formation of FeSi (1 ≤ x ≤ 2). After annealing of a thin Ir layer on Si(100) to 1130 K, a p(2 × 2) LEED pattern with respect to the silicon substrate is observed, which indicates the formation of a well-ordered surface compound. Comparison with the literature shows that the formation of an IrSi species is well known, but only an amorphous and a polycrystalline modification have been described upto now.